PENGARUH PENERAPAN STRATEGI CONTEXTUAL TEACHING AND LEARNING (CTL)TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMP NEGERI 1 GUNUNG TULEH - Aulia, Sindi; Anggraini, Villia; Mardiyah, Ainil (Pendidikan Matematika, 2013)
The research was motivated by the lack of ability of the student in constructing their own knowledge and comprehension of mathematical concept student are still low. Resolve the issue applied a strategy of Contextual Teaching and Learning (CTL). The study aims to determine whether students comprehension of mathematical concepts with conventional learning. This type of research is the design of the random experiment eith the subject. Populasi in this study is the eight grade student of SMPN 1 Gunung Tuleh. Random sampling is done perpetually, as the experiment class is VIII5 class and control class is the class VIII1. This research instrument is the ultimate test with indicator student comprehension of mathematical concepts. Form of test used is a form of essay that valid and reliabel. Based on the test result obtained by the hypothesis P-value = 0,001 at significance level Â = 0,05, since P-value Â , reject H0 and accept H1. Thus, it can be concluded that student comprehension of mathematical consep using strategies of Contextual Teaching and Learning (CTL) is better than the student comprehension of mathematical concepst with convensional learning on eight grade students of SMP Negeri 1 Gunung Tuleh